Parenteral Nutrition Utilization After Implementation of Multidisciplinary Nutrition Support Team Oversight: A Prospective Cohort Study. (November 2016) - Parent, Brodie; Shelton, Marilyn; Nordlund, Megan; Aarabi, Shahram; O'Keefe, Grant
Background: Multidisciplinary nutrition teams can help guide the use of parenteral nutrition (PN), thereby reducing infectious risk, morbidity, and associated costs. Starting in 2007 at Harborview Medical Center, weekly multidisciplinary meetings were established to review all patients receiving PN. This study reports on observed changes in utilization from 2005–2010. Materials and Methods : All patients who received PN from 2005–2010 were followed prospectively. Clinical data and PN utilization data were recorded. Patients were grouped into cohorts based on exposure to weekly multidisciplinary nutrition team meetings (from 2005–2007 and from 2008–2010). Patients were also stratified by location, primary service, and ultimate disposition. Results : In total, 794 patients were included. After initiation of multidisciplinary nutrition meetings, the rate of patients who started PN decreased by 27% (relative risk [RR], 0.73; 95% confidence interval [CI], 0.63–0.84). A reduction in the number of patients receiving PN was observed in both the intensive care unit (ICU) and on the acute care floor (RR, 0.64; 95% CI, 0.53–0.77 and RR, 0.80; 95% CI, 0.64–0.99, respectively). The rate of patients with short-duration PN use (PN duration of <5 days) declined by 30% in the ICU (RR, 0.70; 95% CI, 0.51–0.97) and by 27% on acute care floors (RR, 0.73; 95% CI, 0.51–1.03). Conclusions : Weekly multidisciplinary review of patients receiving PN was associated with reductions in the number of patients started on PN, total days that patients received PN, and number of patients who had short-duration (<5 days) PN use.